Zur Synonymie bei personenbezeichnenden Einwortidiomen – Eine Analyse am Beispiel von Angsthase und seinen Synonymen - Kałasznik, Marcelina (Kalbotyra, 2020)
The subject of this article are selected German one-word idioms that describe the human trait of anxiety. At the center of the investigation is the question of the synonymy of the phraseologisms to be analyzed. The aim of the study is to show to what extent the analyzed phraseological units can be regarded as synonymous and consequently as interchangeable. The analysis is carried out on the basis of the data taken from the DeReKo. The background to the research on this question is provided by considerations over the definition of single-word idioms, which aim to show that, despite their monolexicality, German single-word idioms should be included in the subject area of phraseology. For this, various arguments are presented and discussed in the theoretical part of the article. The appearance of the synonyms in the lexicon is then explained in more detail, and the manner in which the synonymy is manifested in the phraseolexicon is also discussed. It is pointed out that phraseological units can be synonymous both with one another and with other units of the lexicon. However, it should be noted that only the first perspective of the synonymy of phraseological units is examined in the article.